Comparison of Long-Term Antibody Titers in Calves Treated with Different Conjunctival and Subcutaneous Brucella abortus S19 Vaccines - Ali Uslu; Zafer Sayın; Aslı Balevi; Yasin Gulcu; Fırat Ergen; Islam Akıner; Oguzhan Denizli; Osman Erganis (Animals)
Brucellosis is still the most common zoonosis worldwide despite advanced technology and animal husbandry. Since there is still no effective Brucella vaccine for humans, it is crucial to control the disease in ruminants through eradication and vaccination. Although some countries around the world have achieved this circumstance, every country aims to become free of Brucellosis through vaccination, animal movements, and various eradication measures. For this purpose, the Brucella abortus S19 strain has been used safely for about 100 years. However, due to the O-polysaccharide (OPS) antigen in its structure, the antibody response created by the vaccine causes confusion in serological tests. For this purpose, researchers have provided both mucosal immunity and short-term antibody response by using the B. abortus S19 vaccine in conjunctival form instead of subcutaneous form. This study aimed to determine how long the post-vaccination titer levels persisted in animals vaccinated with vaccines from 3 different companies and different routes. In this study, a total of 115 calves aged 3 to 4.5 months were created in five groups, with 23 animals in each group: group 1 (vaccine brand A), group 2 (vaccine brand B), and group 3 (vaccine brand C) received the two-dose conjunctival vaccine, group 4 received the single-dose subcutaneous vaccine (vaccine brand C), and group 5 received the subcutaneous vaccine (vaccine brand C) plus the booster dose conjunctival vaccine (vaccine brand B). Brucellosis antibody titers were monitored each 21 days until the cattle were 26–28 months old. The collected sera were analyzed using the Rose Bengal Plate Test (RBPT), Serum Agglutination Test (SAT), and Complement Fixation Test (CFT), which are the preferred serological methods for Brucellosis eradication plans worldwide. In the conjunctival vaccination groups, only 3 (13%) of the animals in group 1 developed antibody titers one month after vaccination, and there was no antibody response detected against Brucellosis in group 2 and group 3. In animals that were stimulated conjunctivally, the threshold value of 30 International CFT Units (ICFTUs) (for distinguishing between infective titers and vaccination titers) was observed in one animal each in group 1 and group 2 and 0 animal in group 3. It was found that antibody titers turn to Brucellosis negative in all conjunctival vaccine groups at 7 months after vaccination. In groups 4 and 5, the first-month serological screening detected over 30 ICFTUs in 17 (89.47%) animals and 16 (69.5%) animals, respectively. In group 4, CFT titers were found to fall below 30 on the 17th month and 9.3 on the 22nd month. On the 14th month, the CFT titers of group 5 were found to be below 30, and all animals in this group turned negative after the 19th month. It was found that the single dose B. abortus S19 subcutaneous vaccination in calves caused persistent antibodies in 5% of the population. It is believed that persistent and high antibody titers created by subcutaneous vaccines will cause false positivity and create confusion in Brucellosis eradication programs. Therefore, although there is no clear distinction between vaccinated and infected animals, it has been observed that conjunctival Brucellosis vaccines create more stable antibody titers and decrease rapidly compared to subcutaneous vaccines. Based on the results of this study and the advantages of conjunctival vaccines, more effective eradication programs and antibody monitoring can be carried out in vaccinated herds where Brucellosis outbreaks are observed.